DIGGER: exploring the functional role of alternative splicing in protein interactions. Issue Volume 49:Issue D1(2021) (25th September 2020) - Louadi, Zakaria; Yuan, Kevin; Gress, Alexander; Tsoy, Olga; Kalinina, Olga V; Baumbach, Jan; Kacprowski, Tim; List, Markus
Abstract: Alternative splicing plays a major role in regulating the functional repertoire of the proteome. However, isoform-specific effects to protein-protein interactions (PPIs) are usually overlooked, making it impossible to judge the functional role of individual exons on a systems biology level. We overcome this barrier by integrating protein-protein interactions, domain-domain interactions and residue-level interactions information to lift exon expression analysis to a network level. Our user-friendly database DIGGER is available at https://exbio.wzw.tum.de/digger and allows users to seamlessly switch between isoform and exon-centric views of the interactome and to extract sub-networks of relevant isoforms, making it an essential resource for studying mechanistic consequences of alternative splicing.